2008
DOI: 10.1073/pnas.0802743105
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Notch4 signaling induces hallmarks of brain arteriovenous malformations in mice

Abstract: Brain arteriovenous malformations (BAVMs) can cause devastating stroke in young people and contribute to half of all hemorrhagic stroke in children. Unfortunately, the pathogenesis of BAVMs is unknown. In this article we show that activation of Notch signaling in the endothelium during brain development causes BAVM in mice. We turned on constitutively active Notch4 (int3) expression in endothelial cells from birth by using the tetracycline-regulatable system. All mutants developed hallmarks of BAVMs, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
166
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 40 publications
6
166
1
Order By: Relevance
“…S5). We observed, as we have previously published (15)(16)(17), that advanced AVMs exhibited increased SMA staining. Thus, the absence of SMCs in the initial AV shunts is consistent with a capillary origin of AVMs in the Tie2-Notch4* mice.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…S5). We observed, as we have previously published (15)(16)(17), that advanced AVMs exhibited increased SMA staining. Thus, the absence of SMCs in the initial AV shunts is consistent with a capillary origin of AVMs in the Tie2-Notch4* mice.…”
Section: Resultssupporting
confidence: 75%
“…ECs results in spontaneous AVMs in mice (15)(16)(17)21). Although this work has facilitated new research directions regarding the Notch pathway in AVMs, how aberrant Notch signaling leads to AVM remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gene deletion of Dll4 and Hey1/Hey2 in mice leads to reduce expression of the arterial marker Ephrin B2 (22,27,28) and enhanced expression of the venous marker Eph B4 (29). Constitutively active Notch4 increases expression of Ephrin B2 in the brain vasculature and causes cerebral AVMs (10), and loss of function of Ephrin B2 and Eph B4 affects vascular remodeling and intercalation of arterial and venous vasculature (30). We showed that an increase in Ephrin B2 and a decrease in Eph B4 are associated with AVMs in the Mgp −/− mice, which is consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the genes for activin-like kinase receptor 1 (ALK1), a BMP type I receptor, and Endoglin, a coreceptor of ALK1, cause hereditary hemorrhagic telangiectasia (HHT) characterized by the presence of AVMs in multiple organs including the brain (6)(7)(8)(9). Enhanced endothelial Notch signaling, as mediated by constitutively active Notch4, also promotes the formation of brain AVMs, whereas normalization of Notch4 activity results in regression of arteriovenous (AV) shunts (10,11).…”
mentioning
confidence: 99%